Vulcanization reaction of squalene and S8 powder studied by Sulfur K-edge NEXAFS under liquid phase. Issue 1 (10th March 2015) - Yagi, S; Menjo, Y; Tsukada, C; Ogawa, S; Kutluk, G; Namatame, H; Taniguchi, M
Abstract: Vulcanized rubber materials are useful in our surroundings. However, detail structure and reaction are not revealed even in present. Since squalene molecule possesses some same properties compared with natural rubber, we have prepared the samples of vulcanized squalene at 140 °C for several hours. To understand the vulcanization reaction, sulfur K-edge NEXAFS measurements have been carried out for the vulcanized squalene under liquid phase with He-path system and fluorescence detection mode. Moreover, we have tried curve fitting analysis of NEXAFS spectra. The results indicate that the squalene has been vulcanized by the S8 molecule at 140 °C and the S8 molecule length is shortened from 8 to 5-6 after the vulcanization reaction.